Assessment of chemokine serum levels in epithelial ovarian cancer patients - Falcão-Júnior, João Oscar Almeida [UNESP]; Teixeira-Carvalho, Andréa; Can̂dido, Eduardo Batista; Lages, Elisa Lopes [UNESP]; Freitas G, Gustavo Ferreira [UNESP]; Lamaita, Rívia Mara; Bonfim, Lívia Paula Freire [UNESP]; Salera, Rafael Borges [UNESP]; Traiman P, Paulo [UNESP]; Da Silva-Filho, Agnaldo Lopes [UNESP] (My University, 2013)
Aims and background. The study was undertaken to investigate CCL2/MCP-1, CCL3/MIP-1α, CCL4/MIP-1β, CCL5/RANTES and CXCL8/IL-8 women with epithelial ovarian cancer. Methods and study design. Sixteen patients diagnosed with epithelial ovarian cancer and 18 healthy women with no evidence of malign neoplasia (control group) aged from 23 to 89 years (mean ± SEM, 58.7 ± 2.3) were included. The epithelial ovarian cancer patients underwent laparotomy and debulking surgery. Chemokines serum levels were measured by cytometric bead array. Statistical analysis was performed using Mann-Whitney and Kendall's tau. P<0.05 was considered statistically significant for all analyses. Results. The tumor staging (FIGO) was classified into: I in 4 cases (25%), III in 5 cases (31.3%) and stage IV in 7 cases (43.8%). Sera chemokine dosages of CCL2/MCP-1 and CCL4/MIP-1β were lower in epithelial ovarian cancer patients than in the control group (P = 0.021 and P = 0.030, respectively). No significant difference between groups was observed in the levels of CCL3/MIP-1α, CCL5/RANTES and CXCL8/IL-8. No association between the chemokines analyzed and tumor stage was found. The serum level of CCL4/MIP-1β was correlated with CA-125. Conclusions. The study of serum levels of CCL2/MCP-1, CCL3/MIP-1α, CCL4/MIP-1β, CCL5/RANTES and CXCL8/IL-8 chemokines in epithelial ovarian cancer patients identified a down-regulation in CCL2/MCP-1 and CCL4/MIP-1β, which suggests that the two chemokines may play an important role in the pathophysiology of ovarian cancer.
Keywords: CA-125; Chemokines; Cytometric bead array; Immune system; Ovarian cancer